PUBLIC RELATIONS STRATEGY IN BUILDING THE IMAGE OF UIN SUMATERA UTARA AS AN APPLIED ISLAMIC UNIVERSITY IN THE DIGITAL ERA - Nur Hanifah; Nursamsiah Pasya Hasibuan; Amelia Lestari Butar-butar; Defi Nurfajaria; Zulfan Affandi (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah dan Komunikasi, Universitas Islam Bunga Bangsa Cirebon, 2025)
This study aims to describe and analyze the public relations strategies in building the image of the State Islamic University of North Sumatra (UIN-SU) as a campus based on applied Islamic sciences, as well as to identify its challenges and obstacles. This research employs a qualitative approach, with data collected through observation, interviews, and documentation. Data analysis was conducted through data reduction, presentation, and verification, while data validity was tested using triangulation. The findings reveal that UIN-SU’s public relations strategies include: optimizing website management; promoting campus events; implementing Corporate Social Responsibility (CSR) activities through direct community involvement; collaborating with local mass media; strengthening corporate identity; publishing content via social media platforms such as Instagram, TikTok, YouTube, Facebook, and newspapers; persuasive communication with prospective students; and branding efforts targeted at Islamic Senior High Schools, general Senior High Schools, and Vocational High Schools. The internal obstacles involve limited public relations personnel, while external challenges include low student awareness in disseminating campus information and the need to tailor content for Generation Z. This study contributes by offering strategic guidance for Islamic higher education institutions in effectively developing their institutional image through the strengthening of strategic communication and collaboration, particularly in the digital era.